Deep Analysis of Patella caerulea Calcined Shells for Microwave Applications - Uğurlu, Erkan; Karaaslan, Muharrem; Alkurt, Fatih Özkan; Öksüz, Kerim Emre; Duysak, Önder (Fırat University, 2025)
This study investigates the potential application of Patella caerulea shells collected from the Iskenderun Bay as biomaterial in microwave radomes and examines the dielectric properties of shells calcined at 600-1200 °C. At the central frequency of 10 GHz, the real permittivity values for P600, P800, P1000 and P1200 are 3.2, 2.3, 2.4 and 2.5, respectively. The corresponding imaginary parts at 10 GHz are 0.82, 0.44, 0.52 and 0.56, reflecting temperature-dependent variations. The loss factor of shells, particularly at 2.5 GHz, indicates their potential for low-loss applications in communication, such as microwave laminate and radome applications. Moreover, these materials have been integrated to a traditional patch antenna to show feasibility in a microwave system as a substrate layer. At temperatures exceeding 800 °C, slight increase in the CaO peaks was observed in X-ray diffraction spectrum. The thermal gravimetric analysis and differential thermal analysis of shell powder reveal weight loss occurring in two distinct stages and minor endothermic peaks at 125°C and 275°C. The study highlights that microwave antenna radome materials are promising due to their high impedance matching and low-loss properties. This research contributes to the exploration of marine-sourced materials for economic and ecological benefits in the field of microwave technology.

Bu çalışma, İskenderun Körfezi’nden toplanan Patella Caerulea kabuklarının mikrodalga radomelarında biyomalzeme olarak potansiyel uygulamasını araştırmakta ve 600-1200 °C’de kalsine edilmiş kabukların dielektrik özelliklerini incelemektedir. 10 GHz’lik merkezi frekansta, P600, P800, P1000 ve P1200 için reel dielektrik geçirgenlik değerleri sırasıyla 3,2, 2,3, 2,4 ve 2,5’tir. 10 GHz’de karşılık gelen sanal değerleri, sıcaklığa bağlı değişimleri yansıtan 0,82, 0,44, 0,52 ve 0,56’dır. Kabukların, özellikle 2,5 GHz’deki kayıp faktörü, mikrodalga laminat ve radome uygulamaları gibi iletişimde düşük kayıplı uygulamalar için potansiyellerini göstermektedir. Ayrıca, bu malzemeler bir mikrodalga sistemde alt tabaka olarak uygulanabilirliğini göstermek için geleneksel bir yama antene entegre edilmiştir. Bununla birlikte, 800 °C’yi aşan sıcaklıklarda X-ışını kırınım spektrumunda CaO tepelerinde hafif bir artış gözlemlenmiştir. Kabuk tozunun termal gravimetrik analizi ve diferansiyel termal analizi, iki ayrı aşamada oluşan ağırlık kaybını ve 125 °C ve 275 °C’de küçük endotermik tepeleri ortaya koymaktadır. Çalışma, mikrodalga anten radom malzemelerinin yüksek empedans uyumu ve düşük kayıp özellikleri nedeniyle umut verici olduğunu vurgulamaktadır. Bu araştırma, mikrodalga teknolojisi alanında ekonomik ve ekolojik faydalar için deniz kaynaklı malzemelerin keşfine katkıda bulunmaktadır.
Patella caerulea Kalsine Kabuklarının Mikrodalga Uygulamaları İçin Derinlemesine Analizi
Keywords: Engineering Electromagnetics; Mühendislik Elektromanyetiği